Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10